Percepções de pole dance entre mulheres brasileiras - Santos, Ana Júlia Moreira (Universidade Federal de São Carlos, 2025)
Self-esteem refelects the way in which individuals see themselves and understand their importance in the world. The process of building self-esteem can be influenced by various factors, one of which is the cultural environment in which the individual is inserted. As such, visual representations of beauty in the media are a central influence in shaping an individual's ideal about appearance and, consequently, their own self-esteem. Based on the definition of a standard of beauty linked to thinness and social pressure to achieve it, the construction of female self-esteem is closely linked to aesthetics. One of the techniques used by the beauty industry to achieve this standard is physical exercise. Thus, despite exercise being a factor for improving quality of life, the beauty industry has transformed environments that should be for practicing sport into environments that reinforce unrealistic schemas about the ideal body, which can bar people with non-standard bodies from using these places. On the other hand, pole dance studios seem to be an exception to this reality. As such, the practice of pole dance has the potential to be a physical exercise with various positive impacts on women´s physical and mental health. In this study, the effects of an involvement in pole dance on women's self-image and interpersonal relationships were examined. Participants included 91 women aged between 18 and 55, from 9 different Brazilian states, who answered some sociodemographic questions and the Rosenberg Self-Esteem Scale (RAS), and answered some questions about their perceptions of pole dance. There was notable diversity in the profile of the respondents, considering their age, profession, sexual identity, religion and state of residence, as well as differences in the weekly frequency of training, highlighting the openness of this environment to “all women”. The vast majority of participants (96%) reported moderate or high levels of self-esteem, indicating that practicing pole dance may be contributing positively to their self-esteem. Contrary to expectations, no statistically significant relationship was found between the number of months of pole dancing experience and self-esteem (rS = 0.02, p = 0.846). However, there were few women in the sample who had been practicing for less than 3 months, and the effects on self-esteem may occur precisely during this initial period. In the open-ended comments about the effects of practicing pole dance, nearly all the remarks were very positive, with the highest concentration of comments about improvements in self-esteem, relationship with their body and perceptions of their physical capacity. Given the low number of respondents who had spent little time in pole dance classes, in future research it would be important to evaluate women during the first three months of their involvement in pole dance classes. Overall, the results confirm that women who practice pole dance have good levels of self-esteem, and that it is a very welcoming environment for very diverse women. This is evidence that supports the hypothesis that pole dance is a sport that helps women not only with their physical health, but also with their mental health. These results are important for guiding efforts to create healthy sporting environments.
Brazilian women’s perceptions of pole dance
Keywords: Pole dance; Autoestima; Autoimagem; Self-esteem; Self-image; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO